A Brief Review on Primordial Black Holes as Dark Matter - Villanueva-Domingo, Pablo; Mena, Olga; Palomares-Ruiz, Sergio (Frontiers in Astronomy and Space Sciences, 2021)
Primordial black holes (PBHs) represent a natural candidate for one of the components of the dark matter (DM) in the Universe. In this review, we shall discuss the basics of their formation, abundance and signatures. Some of their characteristic signals are examined, such as the emission of particles due to Hawking evaporation and the accretion of the surrounding matter, effects which could leave an impact in the evolution of the Universe and the formation of structures. The most relevant probes capable of constraining their masses and population are discussed.